Criminal Law Enforcement as an Effort to Protect Children from the Crime of Human Trafficking Medan - Jiwel Badawi; Fitria Ramadhani Siregar (International Journal of Law, Crime and Justice, 2024)
With the increasing number of child trafficking cases, the government needs to focus on serious efforts to eradicate this criminal offence. These efforts are not only in the form of law enforcement in a preventive, repressive, and responsive manner, but also efforts related to the recovery or protection of children who are victims of child trafficking after the completion of the criminal justice process which aims to restore the child's future. The research used in this journal is normative legal research. Normative legal research is research that examines the laws and regulations that apply to a legal problem. Normative research with the object of study of legislative documents by studying and examining library legal materials or can be called a study of legal science. Normative legal research tends to place law as a perspective discipline that is only seen in a normative perspective whose research themes include several things such as legal principles, legal systematics, vertical and horizontal synchronisation, legal comparisons and legal history.Efforts that can be made in providing legal protection to children as victims of human trafficking offences in the principle of legality have been regulated in the 1945 Constitution of the Republic of Indonesia and national legal rules in the form of laws and Presidential Regulations and also regulated in international legal provisions that have been adapted into Indonesian positive law. Efforts that can be made to ensure the legal protection of children as victims of trafficking offences.